The indirect and intangible impacts of a telecentre on a rural community - Ghazala, Tabassum; Narayanan, A/L N. Kulathu Ramaiyer; Roger, Harris; Yeo, Alvin Wee (John Wiley & Sons, Inc, 2019)
The paper explores the impact of a telecentre on the community living in Bario, a small village in the highlands of Malaysian Borneo. Specifically, it addresses indirect and intangible impacts on non‐users of telecentre. Thus, far most research studies have primarily focused on direct and tangible impacts of telecentre on its users whilst impact on non‐users is least covered and understood. Consequently, it was equally essential to study the concept of unquantifiable intangible impacts experienced by the non‐users. Sen's “Capability Approach” (CA) was adopted to understand the impact of telecentre on human development. “The Most Significant Change” (MSC) was employed as a tool for collecting data in the form of stories from the telecentre users and non‐users. The process involved gathering stories about the telecentre impact from the Bario community people. The MSC stories with significance relevance were identified and selected with the help of the community. Those were then analysed using the content analysis technique and Leximancer to identify the patterns of change experienced by the respondents. The results of the study on the whole suggests that the Bario community has benefited from the use of the telecentre, both directly and indirectly, including intangible impacts such as connectedness, a sense of belongingness, strengthened social ties, and psychological empowerment (selfesteem and self‐efficacy). The theoretical approach together with methodological approach provided a base for understanding ways to conceptualize the development and determine the ways in which telecentre contributed directly or indirectly to the social and economic development of the community inhabitants.